THE INTERRELATIONSHIP BETWEEN SELF-CONFIDENCE AND SPEAKING ACHIEVEMENT - Muhammad Alif Firdaus; Eko Suhartoyo; Dzurriyyatun Ni'mah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The current research applied quantitative design in order to compute the numerical data. The research design used correlational design and independent sample t-test. The researcher took 33 students to serve as the sample of the study. The data covered the students’ self-confidence level and their speaking score. The findings of the research indicated that the majority of the students (61%) reached high self-confidence in working on the questionnaire, while the majority of the students (76%) reached the average score in their speaking achievement. According to the correlational results, the data showed that the sig. (2-tailed) was .610 which means it was higher than the significant value (0.05). It could be inferred that there was no significant correlation between self-confidence and speaking achievement. Meanwhile, based on the results of independent sample t-test, the level of significance (p-value) was .000 which means the p-value was lower than the significant value (0.05). It could be concluded that there was a significant difference between the students who have high self-confidence and the students who have low self-confidence in their speaking achievement. In sum, it can be stated that the students who have high self-confidence do not determine they will also achieve high speaking achievement.Keywords: Relationship, Speaking Skill, Self-confidence